DAMPAK UPAH MINIMUM DAN INFLASI TERHADAP PENGANGGURAN - Lisa, Miftakhul Khoirul; Vinsentia, Krista Bella; Octavia, Ayu Nurafni (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2024)
The purpose of this study is to determine the effect of minimum wages on unemployment, and inflation on unemployment in 5 cities in Central Java Province, namely Cilacap, Surakarta, Kudus, Semarang, and Tegal in 2016 - 2021. The type of data used in this study is secondary data that has been published in the form of time series data for 6 years in Central Java Province. The data source obtained from the Central Statistics Agency (BPS) of Central Java Province related to the variables of minimum wages, inflation and unemployment rates from 2016 - 2021. This study uses a prerequisite analysis test in using multiple linear regression analysis with the classical assumption test. Determination test (R2), Simultaneous Test (F) and partial test (t). The results of this study indicate that partially the minimum wage has a positive and significant effect on the unemployment rate in 5 cities in Central Java Province in 2016 - 2021. Inflation has no effect on unemployment in 5 cities in Central Java Province in 2016 - 2021. Simultaneously, the minimum wage and inflation have an effect on unemployment